The potential of short-chain fatty acid epigenetic regulation in chronic low-grade inflammation and obesity - Kopczyńska, Julia; Kowalczyk, Magdalena (Frontiers in Immunology, 2024)
Obesity and chronic low-grade inflammation, often occurring together, significantly contribute to severe metabolic and inflammatory conditions like type 2 diabetes (T2D), cardiovascular disease (CVD), and cancer. A key player is elevated levels of gut dysbiosis-associated lipopolysaccharide (LPS), which disrupts metabolic and immune signaling leading to metabolic endotoxemia, while short-chain fatty acids (SCFAs) beneficially regulate these processes during homeostasis. SCFAs not only safeguard the gut barrier but also exert metabolic and immunomodulatory effects via G proteincoupled receptor binding and epigenetic regulation. SCFAs are emerging as potential agents to counteract dysbiosis-induced epigenetic changes, specifically targeting metabolic and inflammatory genes through DNA methylation, histone acetylation, microRNAs (miRNAs), and long non-coding RNAs (lncRNAs). To assess whether SCFAs can effectively interrupt the detrimental cascade of obesity and inflammation, this review aims to provide a comprehensive overview of the current evidence for their clinical application. The review emphasizes factors influencing SCFA production, the intricate connections between metabolism, the immune system, and the gut microbiome, and the epigenetic mechanisms regulated by SCFAs that impact metabolism and the immune system.